2011
DOI: 10.1080/1357650x.2010.485353
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual asymmetries in the discrimination of brief auditory time intervals

Abstract: This experiment was conducted to determine whether perceptual asymmetries would emerge in a task requiring the discrimination of two auditory time intervals. The first interval (standard) was presented binaurally and the other one (comparison) monaurally. The intervals were either filled (continuous sound) or empty (duration between two brief sounds). A total of 24 right-handed participants (12 women, 12 men) completed the four conditions (two Ear×two Structure). The results revealed that filled intervals were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…This interpretation is also supported by the higher hit rates during presentation of tones to the right ear than to the left ear. This left-lateralized processing corresponds to several other studies suggesting left-lateralized processing of duration during a categorization Puschmann et al, 2013] or comparison task [Brancucci et al, 2008;Grondin et al, 2011;Mills and Rollman, 1979;Reiterer et al, 2005]. A previous study also showed an involvement of the left and right AC in duration categorization [Angenstein and Brechmann, 2013a].…”
Section: Activity In the Auditory Cortexsupporting
confidence: 88%
See 3 more Smart Citations
“…This interpretation is also supported by the higher hit rates during presentation of tones to the right ear than to the left ear. This left-lateralized processing corresponds to several other studies suggesting left-lateralized processing of duration during a categorization Puschmann et al, 2013] or comparison task [Brancucci et al, 2008;Grondin et al, 2011;Mills and Rollman, 1979;Reiterer et al, 2005]. A previous study also showed an involvement of the left and right AC in duration categorization [Angenstein and Brechmann, 2013a].…”
Section: Activity In the Auditory Cortexsupporting
confidence: 88%
“…For example, in tasks requiring a direct comparison of the duration of two sounds, the majority of studies suggest a left‐lateralized processing ([Brancucci et al, ; Grondin et al, ; Mills and Rollman, ; Reiterer et al, ] but see Bueti et al []). In contrast, studies in which the duration of sounds could be evaluated in a categorical manner led to controversial results with left lateralized [Brechmann and Scheich, ; Puschmann et al, ] or right lateralized results [Angenstein and Brechmann, ; Buchtel et al, ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our initial analyses, we found that left-handedness, albeit with only 9 participants, seemed to have a significant influence on the effect of duration on discrimination performance, F(1, 72) = 4.13, p = .04, η 2 = .05, with those who were left-handers producing higher long thresholds (M = 203.5 ms, SE = 28.4) than right-handers (M = 140.8 ms, SE = 9.9) but not short thresholds. Given that there is some evidence that laterality has an influence on time perception with the right hemisphere being related to visual information processing and left hemisphere to specialized timing processes (see Grondin & Girard, 2005;Grondin, Voyer, & Bisson, 2011;Polzella, DaPolito, & Hinsman, 1977), we decided to exclude data provided by left-handed participants from further analysis in order to reduce this noise in the data rather than attempt to account for the added variability statistically.…”
Section: Experiments 2 Methodsmentioning
confidence: 99%